Városmarketing mint a helyi gazdaságfejlesztés egyik lehetséges eszköze - Kozma, Gábor (Tér és Társadalom, 1995)
City marketing – as a new, market-oriented approach of urban policy – has been focused on in the West European and North American big cities since the second half of the 1970s. The self governments of the Central European countries have paid greater and greater attention to this topic since the sytemic change, too. In the background of the special interest in city marketing, we can see those European and American changes (e.g. the growth of the service sector, the development of the transport and information technology, the failure of the formerly applied regional-planning methods) that have significantly weakened the economic bases of the towns. This made the self governments realise that they had to play a much more initiative role in shaping the future of their towns: lt is not enough to control development but it has to be effíciently supported. The author attempts to introduce the most important characteristics of this new type of urban policy. First he seeks the answer to the question of where the differences between city marketing and traditional marketing are. In his opinion the differences appear especially with respect to the „product to be marketed": Towns have special features (e. g. they are much more complex and much less flexible than traditional products, they are situated in a spatial context), which factor has an intluence on the whole marketing process. In the second part of the essay the author deals with the specific parts of city marketing, stressing that the neglect of any element can endanger the success of the whole process. The first very important task is the survey of the inner and outer environment of the settlement, as a result of which the self government can obtain a broad picture of the situation of the town. Simultaneously, the self government has to try to develop the endowments, which contains four fields. It has to provide the infrastructural bases of further development, also, it has to create a suitable co-opearation between the organs involved in the marketing activity. It has to establish an attractive image of the town as well as to create attractions that can attract visitors to the town. The following important element of city marketing is market segmentation, which means the choice of the target groups that the self government wants to attract. During this process, the relationship of the specific target groups to the seftlement has to be analysed and those market segments have to be specified for which the town can offer advantages that awake the interest of the given group. In the last step the self government has to appear in the market and it has to strive, using different means, to create a favourable image of itself. In the framework of this, it has to plan, on the one hand, a face and a message carrying it that can convince people of the advantages of the given region, on the other hand, this message has to be transferred to the specific market segments. During this process the different needs of the certain target groups (e.g. tourists, actors of business life) have to be taken into consideration and the self government has to find where these groups (as consumers) are in the purchasing process.